3D modeling using laser scanning for reverse engineering applications : verification test - Khairulazhar Zainuddin, author; Halim Setan, 1957-, author; Zulkepli Majid, author; Azran Hazemi Jusoh, author; International Symposium and Exhibition on Geoinformation (2009 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL